NOVEL KOMIK SEBAGAI MEDIA PEMBELAJARAN DAN DAKWAH AL-ISLAM KEMUHAMMADIYAHAN - Anip Dwi Saputro (ISTAWA, 2016)
The progress of time, making the preaching activity is now not as difficult as the time of the Prophet. Many ways in which to convey Islam, and became one of the comic novel. It also brings a major breakthrough to ground or publish the hadits of the Prophet, as well as showing the meaning of jihad from a different perspective. Following the progress of time, Islam also demanded that the teaching creative entry to the young people in an appropriate manner but still on track justified.Comic novel (nomic) seen from the title might be a lot to think if nomic's more appropriate for small children, but not if you look at the contents of nomic. Where the values contained in this comic is not merely as entertainment, but of delivering the universal message of the Prophet through his word. This paper examines the comic novel (nomic) as a medium for the propagation of Al-Islam Kemuhammadiyahan on novel and comic book lovers community. Today, Islam and Kemuhammadiyahan it should be taught new ways to fit the spirit of the present generation. One of them through comic novel.Comic novel can be said to contain a spiritual message, if it contains material that educates human spiritual. So as to bring the reader to the direction in accordance with the purpose of propaganda of Al-Islam Kemuhammadiyahan. Instead novels and comics can be categorized useless, if it does not contain messages that educate the reader, even contain messages that are contrary to the noble message of humanity.It thus becomes clear that in the literature there is a process of communication (messaging), the author of the society as a reader. Therefore the literature can be used as a medium of propaganda because it contains messages that can be included as a matter of propaganda.